Identifying the source of peritoneal carcinomatosis by molecular biological method (a clinical case) - K.R. Ishmuratova (LCC «Medicine-Inform», 2023)
K.R. Ishmuratova1,2 1Bashkir State Medical University, Ufa, Russian Federation 2Republican Clinical Oncological Dispensary, Ufa, Russian Federation In recent decades, multiple biological markers have been discovered which demonstrate a high specificity in determining tumor phenotypes. There has been much debate on their role in differentiating the origin of metastasis. This article presents a clinical case of peritoneal carcinomatosis arising from breast carcinoma. The immunohistochemical method was used to determine the tumor phenotype. For this purpose, the markers of gastrointestinal, ovary and breast tumors were utilized, including CDX2, PAX 8, WT1, CK7, CK20, Mammaglobin, and GCDFP-15. The findings of molecular biological phenotyping confirmed the diagnosis of primary multiple malignant neoplasms with peritoneal carcinomatosis arising from breast carcinoma. More accurate identification of tumor phenotypes plays an important role in predicting the disease outcome and specifying indications for prescribing anticancer drug treatments. The described clinical case demonstrates that molecular biological phenotypin g can be used as a proving method for identifying the origin of peritoneal carcinomatosis. The development of a panel of markers for different tumor localizations will allow a reliable detection of the source of peritoneal carcinomatosis. In cases of diagnosing peritoneal carcinomatosis from tumors with an undetected primary lesion, such panel of biological markers will help to reduce the time of examination and improve the quality of medical care. Keywords: peritoneal carcinomatosis, diagnosis, biological markers, immunohistochemistry, breast cancer, ovarian cancer, colorectal cancer, gastric cancer. For citation: Ishmuratova K.R. Identifying the source of peritoneal carcinomatosis by molecular biological method (a clinical case). Russian Journal of Woman and Child Health. 2023;6(1):31-33 (in Russ.). DOI: 10.32364/2618-8430-2023-6-1-31-33.